Collaboration and extended techniques in “Interferência”: from conception to performance - Batista Júnior, José (Programa de Pós-Graduação em Música da UFRJ, 2021)
This paper describes the collaborative process between composer and interpreter in the composition and performance of a work for bass clarinet and electronics entitled Interferência (Interference). In addition to a contextualization, where we discuss collaboration in music and extended techniques, the work’s compositional process is explained to demonstrate the role of collaboration in its development. The challenges presented by the use of microtonalism and the extensive use of some instrumental techniques, still seen as extended in some contexts, are approached practically. The technical solutions achieved are demonstrated through various audio and video examples, including the final performance.